Study of mitigation of superheater tube failure & maintenance of an industrial boiler / Sri Ganesh Elangkovan - Sri Ganesh , Elangkovan (2019)
As new industries and technologies emerges, the utilization of boilers never fades and it there all over the world. A boiler is a crux of most industries whereby it produces steam, hot water and etc for production purpose, steam turbine and etc. In this paper we concentrate on the water tube boiler due the relevance of the topic. Most industries relies on the steam turbine to generate electricity for production purposes and this requires usage of steam generated by boilers for their operation. Other than that, steam turbine requires dry steam and not saturated steam which most industries utilizes for production. The dry steam is produces by passing through one of a critical component of boiler which is the superheater. Superheater is required in order for the boiler to produce dry steam or also known as superheated steam. As a critical component, this superheater is prone to failure due exposure of high temperature constantly and to mitigate it, the paper studies method and ways to minimize and prevent the failure of superheater tube and also maintenance of an industrial boiler for better efficiency.